Pentingkah Pengaruh Lingkungan Kerja Disiplin Dan Motivasi Terhadap Kepuasan Kerja Karyawan - Hamdan; Amarul; Ratu Erlina Gentari (Universitas Serang Raya, 2022)
This study aims to determine the effect of the work environment, discipline, and motivation on employee job satisfaction at PT Elnusa Fabrication Construction in Cilegon City. This research was conducted using quantitative research methods. The research population was conducted at PT Elnusa Fabrication Construction in Cilegon City totaling 52 people, and samples were taken using a saturated sample. The research was conducted at PT Elnusa Fabrication Construction in Cilegon City from 19 November 2021 to 19 August 2022. Data was collected using a questionnaire (questionnaire), and analyzed using the SPSS application version 25. Based on the results of the study it can be concluded that there is a significant influence between the work environment and employee job satisfaction, there is a significant influence between work discipline and employee job satisfaction, there is a significant influence between work motivation and employee job satisfaction, and there is a significant influence between work environment, discipline, and motivation simultaneously on employee job satisfaction. researchers who will conduct research at the same location as this study, should use other variables that have not been studied at the same location to develop research.